Molecular genetics of resistance to Spongospora subterranea f. sp. subterranea infection in potato (Solanum tuberosum L.) - Van der Waals, Jacqueline Elise (University of Pretoria, 2024)
Thesis (PhD (Plant Pathology))--University of Pretoria, 2020.